MOTIVASI DAN MINAT MAHASISWA BERWIRAUSAHA - Rahma Faelasofi (Universitas Muhammadiyah Pringsewu, 2018)
Nowdays, many entrepreneurship arose, it caused one of the subject came from a group who are studying such as university students. It was in line with subject entrepreneurship as a way for students open-minded in doing entrepreneurship. Thus, by giving that subject, the objective of the research is to know how big the students motivation and interest in doing entrepreneurship. The method of this research was sampling method. This research was quantitative research. The subject of the research was students of STKIP MPL. The source of data was primer data. The data collecting technique was questioner and interview. Data analysis was simple regression. The result of this research was there is significant influence which is shown that value of determination coefficient of students motivation towards students interest was 13,3%. Keywords: motivation, interest, simple regression.